2008
DOI: 10.1002/adsc.200800253
|View full text |Cite
|
Sign up to set email alerts
|

Proline‐Mediated Enantioselective Construction of Tetrahydropyridines via a Cascade Mannich‐Type/Intramolecular Cyclization Reaction

Abstract: A highly diastereo-and enantioselective synthesis of 2,3-disubstituted tetrahydropyridines was accomplished via a proline-mediated cascade Mannich-type/intramolecular cyclization reaction from preformed N-PMP (p-methoxyphenyl) aldimines and inexpensive aqueous tetrahydro-2H-pyran-2,6-diol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In 2008, Xu and coworkers [26] reported an enantioselective synthetic method for substituted tetrahydropyridines via a proline-mediated cascade Mannichtype/intramolecular cyclization (Scheme 16). A noteworthy advantage of the method was the NPMP aldimines from inexpensive aqueous materials tetrahydro-2H-pyran-2,6-diol were easily prepared with excellent diastereo-and enantioselectivity in the presence of water.…”
Section: L-proline and Its Derivativesmentioning
confidence: 99%
“…In 2008, Xu and coworkers [26] reported an enantioselective synthetic method for substituted tetrahydropyridines via a proline-mediated cascade Mannichtype/intramolecular cyclization (Scheme 16). A noteworthy advantage of the method was the NPMP aldimines from inexpensive aqueous materials tetrahydro-2H-pyran-2,6-diol were easily prepared with excellent diastereo-and enantioselectivity in the presence of water.…”
Section: L-proline and Its Derivativesmentioning
confidence: 99%
“…Xu and co‐workers reported a diastereo‐ and enantio‐selective synthetic protocol by the application of glutaraldehyde ( 24 ) to produce N ‐heterocycles such as tetrahydropyridines by using primary amine catalysis. A Mannich‐type reaction was developed, which gave 25 in an intramolecular aqueous cyclization of glutaraldehyde, N ‐PMP aldimine 26 and proline ( 27 ) providing the corresponding tetrahydropyridine derivative 28 (Scheme ) …”
Section: Synthesis Of Saturated N‐heterocycles From Dialdehyde Compoundsmentioning
confidence: 99%
“…A Mannich-type reaction was developed, which gave 25 in an intramolecular aqueous cyclization of glutaraldehyde, N-PMP aldimine 26 and proline (27) providing the corresponding tetrahydropyridine derivative 28 (Scheme 3). [46] Kumar et al reported an extension of the above-described procedure. Cycloaddition of glutaraldehyde (24) furnished asymmetric 2,3-disubstituted piperidine framework (29) with reduction in the last step (Scheme 4).…”
Section: Transformation Of Linear Dialdehydes Into N-heterocyclesmentioning
confidence: 99%
“…1, Scheme 13). 37 This rapid approach involved aldimines 21 derived from aromatic/heteroaromatics/alkenyl aldehydes through proline 2 mediated direct Mannich reaction with glutaraldehyde 37 followed by intramolecular cyclization as one-pot 20 transformation. Recently, Kumar and co-workers documented another interesting application of glutaraldehyde 37 for the asymmetric synthesis of 2,3-substituted piperidines 67 through the [4+2] annulation strategy (eqn.…”
Section: Glutaraldehydementioning
confidence: 99%